Distribution of surface heat flow and effects on the subsurface temperatures in the northern part of Thrace Basin, NW Turkey - ERKAN, KAMİL (My University, 2023)
The Thrace Basin in northwestern Turkey is a deep Eocene–Oligocene hydrocarbon-bearing sedimentary basin. The basin has potential for geothermal energy utilization in the future due to its favorable geological conditions. In this study, we combined the available bottom hole temperature (BHT) data from 70 points with the thermal conductivity and radiogenic heat productions of the basin formations, and generated a detailed thermal model of the northern part of the basin. For heat flow determinations from the BHT data, we applied Bullard’s thermal resistance method on formation thermal conductivities and thicknesses. The results give an average surface heat flow of 65.8 ± 11.3 mW/m2. We obtained high heat flow values (75–80 mW/m2) in the eastern and western sides, and the central part of the study area. These relatively high heat flow values can be explained by the combined effect of basement topography and the variations in the radiogenic heat production of the basement rocks. The calculated subsurface temperatures in selected hydrocarbon fields vary in the range of 45–64 °C at 1 km depth, 99–136 °C at 3 km depth, and 155–208 °C at 5 km depth as a result of local variations of the surface heat flow and formation thermal resistances. These variations in subsurface temperatures can have significant effects on the cost of geothermal energy production in future.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Jeoloji Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Geological Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Yerbilimleri; ENERJİ VE YAKITLAR; YER BİLİMİ, MULTİDİSİPLİNER; JEOLOJİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; GEOSCIENCES; ENERGY & FUELS; GEOSCIENCES, MULTIDISCIPLINARY; GEOLOGY; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Geoteknik Mühendisliği ve Mühendislik Jeolojisi; Ekonomik Jeoloji; Renewable Energy, Sustainability and the Environment; Physical Sciences; Geotechnical Engineering and Engineering Geology; Economic Geology; Heat flow; Thrace Basin; Geothermal; Bottom-hole temperature; Bullard's method; ANATOLIAN FAULT; EVOLUTION; WESTERN; TECTONICS; PONTIDES; HISTORY; SYSTEM; REGION; ZONE; OIL; Bullard’s method; Heat fow; Thrace Basin; Geothermal; Bottom-hole temperature; Bullard’s method